2003
DOI: 10.1002/ajh.10254
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilic genotypes, natural anticoagulants, and plasma homocysteine in myeloproliferative disorders: Relationship with splanchnic vein thrombosis and arterial disease

Abstract: The contribution of pro-thrombotic factors towards the development of arterial disease (AD) and splanchnic vein thrombosis (SVT) was retrospectively evaluated in 79 patients (39M, 40F, mean age 55 ± 16 years) with myeloproliferative disorders (MPD) (essential thrombocythemia [n = 26], primary proliferative polycythemia [n = 27], and idiopathic myelofibrosis [n = 26]). Of these, 18 had AD and 17 SVT, the remaining 44 were nonthrombotic (NT). Plasma concentrations of natural anticoagulants, plasma homocysteine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
4
32
2
1
Order By: Relevance
“…8 The systematic review and meta-analysis of 2,436 patients with ET shows that JAK2 positivity correlated with a clear increase in the odds of thrombosis (OR = 1.83) 9 , and this was also observed by others. [10][11][12] Our findings are in line with the results of Schwartz et al, 13 who have proven, on the basis of an analyzed cohort of 1,179 thrombocythemic Ph-myeloptroliferations, that JAK2 mutation affected significantly the incidence of thrombosis (both arterial and venous). The JAK2 mutation has been included recently into the major criteria for ET 14,15 , and is also considered as a major prothrombotic risk factor in the International Prognostic Score in Essential Thrombocythemia (IPSET) risk factor study in WHO-defined ET.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…8 The systematic review and meta-analysis of 2,436 patients with ET shows that JAK2 positivity correlated with a clear increase in the odds of thrombosis (OR = 1.83) 9 , and this was also observed by others. [10][11][12] Our findings are in line with the results of Schwartz et al, 13 who have proven, on the basis of an analyzed cohort of 1,179 thrombocythemic Ph-myeloptroliferations, that JAK2 mutation affected significantly the incidence of thrombosis (both arterial and venous). The JAK2 mutation has been included recently into the major criteria for ET 14,15 , and is also considered as a major prothrombotic risk factor in the International Prognostic Score in Essential Thrombocythemia (IPSET) risk factor study in WHO-defined ET.…”
Section: Discussionsupporting
confidence: 81%
“…10 Schwartz et al have shown that in ET the specific thrombophilic markers, e.g. FVLeiden mutation and protein C deficiency, were connected with thrombotic venous events.…”
Section: Discussionmentioning
confidence: 99%
“…In the general Caucasian population the prevalence of the PT 20210A allele is 2% showing difference according to geographic variation approximately 2%, with some geographic variation [5]. The prevalence of FVL and PT mutation in Turkey was reported to be 7.4%-10.8% and 2.6%, respectively [6][7][8][9][10], which differs from the reported incidence of FVL and PT mutation in patients with ET and PV [11][12][13]. To the best of our knowledge the frequency of FVL and PT mutation in patients with IMF has not been reported.…”
Section: Introductioncontrasting
confidence: 48%
“…68 Several studies have demonstrated elevated homocysteine levels among patients with MPN. 69,70 Many MPN patients develop hyperhomocysteinaemia during the course of the disease, 71 and this has been attributed to vitamin folic acid deficiency. 72 Hyperhomocysteinaemia is likely to increase the thrombotic risk of MPN patients.…”
Section: Genetic and Acquired Thrombophiliamentioning
confidence: 99%